If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 59 + -1b = 72 Solving 59 + -1b = 72 Solving for variable 'b'. Move all terms containing b to the left, all other terms to the right. Add '-59' to each side of the equation. 59 + -59 + -1b = 72 + -59 Combine like terms: 59 + -59 = 0 0 + -1b = 72 + -59 -1b = 72 + -59 Combine like terms: 72 + -59 = 13 -1b = 13 Divide each side by '-1'. b = -13 Simplifying b = -13
| 4x+3(x+3)=184 | | 2(p+1)+2=6 | | -7(a-2)=27 | | -18b-27=45 | | 1/2(3p-1)5 | | 95=5x+10 | | 3.25x-2.5=2.7x+3 | | s-20/-2=0 | | Page=6(a+4) | | (-8b+13d)-14b= | | -2(b+11)=16 | | 5m+15=-23 | | 2(v-6)+2=8 | | (y((x^3)-(y^5)))dx-(x((x^3)+(y^5)))dy=0 | | 2*b=14+3b | | 2(v-19)=-2 | | a*34=7a+3*34 | | 9y+15y=45 | | a*32=7a+3*32 | | .5a-54=.5a | | a*30=7a+3*30 | | Y+15=y | | 28x=19.8 | | 3e^2=x | | 4(w-1)=-16 | | 18a+2a-16a-2a=10 | | 1y-8-2=5 | | 4x=3x-14 | | a*24=7a+3*24 | | (3x-4)(x-9)=(x-10)(2x-8) | | 28x=18.8 | | -18n-n+17n=18 |